Cultivation, production and management techniques of broom grass (Thysanolaena maxima Roxb.) in hilly areas of Bangladesh - Alam, Mohammod Jahangir; Islam, Sayed Mohammod Zahirul; Rahman, Mohammod Motiar (Agriculture and Natural Resources, 2017)
This paper presents the results on appropriate cultivation, plantation, production and management techniques of Thysanolaena maxima for domestication at age 1-4 yr (grown 2007-2011). Rhizome cuttings were planted in research experimental plots at spacings of T1=1.0 m x 1.0 m, T2= 1.5 m x 1.5 m and T3 = 2.0 m x 2.0 m in a randomized complete block design with six replications and three treatments. The results showed that the number of panicles produced was 1048, 41,237, 78,737 and 105,094 in year 1 to year 4, respectively. The average total green weight (kg/plot) was 10.26, 632.15, 423.34 and 543.40 and the average dry weight (kg/plot) was 9.88, 287.65, 216.93 and 241.60 in year 1 to year 4, respectively. Composite soil samples were collected and the soil pH values of the surface soil from the different treatments varied from 5.1 to 5.2. There was no significant difference among the treatments in the available P and S. The available Ca, Mg and K were higher in the T3 treatment compared with the other treatments. Planting rhizome cuttings at 2.0 m x 2.0 m spacing gave the maximum broom/panicle production.